1993
DOI: 10.1111/j.1365-2214.1993.tb00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep management — the hidden agenda

Abstract: The management of apparent sleep problems is often not straight-forward because of a proportion of clients attending with a 'hidden agenda', requiring more in-depth long-term treatment for psychological problems. This paper looks at a sample of 100 consecutive referrals to a community sleep clinic in the East End of London and attempts to address the question of who comes to the sleep clinic and why. A proportion of clients responded to brief intervention of a behavioural nature but 19% were referred on to oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Also associated with waking frequency was mother’s educational level, but this was correlated negatively with waking. We pointed earlier to the fact that children with sleep problems frequently come from families where educational levels are low and social stressors are high (Scott & Richards 1990; Walters 1993; Kerr & Jowett 1994). It is likely that these problems combine to produce an environment where sleep problems can flourish.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Also associated with waking frequency was mother’s educational level, but this was correlated negatively with waking. We pointed earlier to the fact that children with sleep problems frequently come from families where educational levels are low and social stressors are high (Scott & Richards 1990; Walters 1993; Kerr & Jowett 1994). It is likely that these problems combine to produce an environment where sleep problems can flourish.…”
Section: Discussionmentioning
confidence: 97%
“…Researchers have shown that teaching parents to solve their children’s sleep problems generally results in a reduction of maternal stress (Quine 1992a; Wolfson et al 1992; Wiggs 1996). However, the issue is complex (Walters 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The current study describes parental beliefs about child sleep problems in Rett syndrome, along with coping behaviours and emotional factors. As difficulty complying with behavioural interventions for sleep disturbance has been identified in some families (Walters 1993), the importance of addressing cognitive and emotional factors in parents is highlighted. The proposed model could be utilised to guide assessment in clinical practice and identify beliefs and attributions, which may influence behaviour and potentially impede any behavioural treatment for sleep disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…The therapists reported that about 30% of families came to the first interview without fathers, and that fathers were more resistant than mothers about subsequently returning to the clinic. In another study it was found that attendance by fathers at a child community sleep clinic was 31% and that two-thirds of these fathers were in the professional occupational group (Walters, 1993).…”
Section: Attendance By Fathersmentioning
confidence: 98%